UPAYA MENINGKATKAN KEMAMPUAN BERHITUNG PERMULAAN MELALUI TABUNG ANGKA PADA ANAK USIA 5-6 TAHUN - Astuti, Eka Setiawati, Subhan (JURNAL PENDIDIKAN DAN PENELITIAN SERUMPUN MENGAJAR, 2024)
This study aims at (1) To improve the ability to calculate beginnings through the media of a number tube in a child aged 5-6 years in PAUD Ar Rohman Prefecture Tunjung Teja (2) To improve the ability to calculate the beginnings through the media of the number tube in children aged 5-6 years in PAUD Ar Rohman Prefecture Tunjung Teja. Guide I: Eka Setiawati, M.Pd. Guide II: Subhan, M.Pd. Buddhist Faithful University (USB) Rangkasbitung 2024. The research method used in this study is the Class Action Research (PTK) method which consists of two cycles and each cycle has three meetings. Subjects of this research, which is the age of 5-6 years in PAUD Ar Rohman Prefecture Tunjung Teja. Guides. Research data collection techniques, that is, through observation, and documentation. The results of the research showed that learning through digital media can improve the ability of 5-6-year-olds to start counting in the PAUD Ar Rohman Prefecture of Tunjung Teja district of Serang. The rate of success in children is increasing. In pre-cycle activity from an average of 62.67% increased 10.33% in cycle I to 73.00% then increased another 4.33% at cycle II to 77.33%.